THE ROLE OF AMIR TEMUR IN WORLD HISTORIOGRAPHY AND SOURCE STUDIES (Innovative Technologica: Methodical Research Journal, 2023)
This article provides information about the role of Amir Temur in World historiography and source studies and the preparation of Amir Temur for military campaigns.